PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENUMBUHKAN KARAKTERISTIK PADA ANAK USIA DINI - Muzdalifah, Fithrii (LPPM Institut Pendidikan Nusantara Global, 2021)
Human resource development was the development of individuals, groups or communities by providing knowledge, expertise, and experience so that they can carry out their roles and responsibilities in society. Problems that occur in parenting include: Parents give freedom to children to watch TV without supervision, give children to play PS, give gadgets to children, spoil children, compare children, and it is not uncommon to even scold and even hit children. One of the activities that can be done in human resource development is